A descriptive cross-sectional study on COVID-19 knowledge, attitude, and practices of South Indian population - Shakeer Kahn Patan; Sravana Deepthi Chittem; Pallavi Madithati; Bayapa Reddy Narapureddy; Chandra Sekhar Chittooru; Kalyan Viswanath Reddy Lingala; Kumar Gular (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The 2019-novel coronavirus (2019-nCoV) started as an epidemic later transformed into a pandemic causing a threat to public health globally. Any community to fight the COVID-19 pandemic requires adequate knowledge, attitude of the people, and practice of the government-imposed laws and regulations. Based on these factors, we framed the objectives to find the sociodemographic profile of the study group and to assess their knowledge, attitude, and practice (KAP) toward COVID-19. These results will help the health planners and administrators in each state to find out the gap in health education efforts. MATERIALS AND METHODS: A descriptive, cross-sectional study was conducted on South Indian population to know KAP toward COVID-19. A convenient sampling technique was used to collect the data using Google forms, and analysis was done using the SPSS software version 21. The questionnaire includes sociodemographic information, KAP questions toward COVID-19, and perception toward national and community responses. RESULTS: A total of 1644 were participated; the average knowledge score was 17.5 (+1.9). Most of them (92.9%) respondent's perceived that early detection will have a better outcome from COVID-19, whereas the knowledge compared with practice, there is a significant difference Pearson correlation (0.404) P is < 0.001. CONCLUSIONS: Although a high level of knowledge on COVID-19 in the public gradually decreasing the practice of preventive measures, the government should continue the consistent efforts to change the behavioral communication and motivate the public social responsibility to adhere to the health protocols, masking, hand hygiene, social distancing, and vaccination to prevent expected COVID-19 subsequent episodes.